Small molecule, NSC95397, inhibits the CtBP1-protein partner interaction and CtBP1-mediated transcriptional repression - Blevins, Melanie A. (J Biomol Screen, 2014)
Carboxyl-terminal binding protein (CtBP) is a transcriptional co-repressor that suppresses multiple pro-apoptotic and epithelial genes. CtBP is overexpressed in many human cancers and its overexpression increases stem cell-like features, epithelial-mesenchymal transition, and cancer cell survival. Knockdown of CtBP increases apoptosis independent of p53 and dramatically inhibits tumorigenesis in mouse models. Therefore, targeting CtBP with small molecules that disrupt its interaction with transcription factor partners may be an effective cancer therapy. To elicit its co-repressing effect, CtBP binds to a conserved peptide motif in each transcription factor partner. We developed an AlphaScreen high throughput screening assay to monitor the interaction between CtBP and E1A (which mimics the interaction between CtBP and its transcriptional partners). We screened the LOPAC library of 1280 bioactive compounds and identified NSC95397, which inhibits the CtBP-E1A interaction (IC(50) = 2.9 μM). The inhibitory activity of NSC95397 was confirmed using two secondary assays and a counterscreen. NSC95397 also behaved as a weak substrate of CtBP dehydrogenase activity and did not inhibit another dehydrogenase, LDH. Finally, NSC95397 was able to disrupt CtBP-mediated transcriptional repression of a target gene. These studies present a new possibility for the development of a therapeutic agent targeting tumors through disrupting the CtBP transcriptional complex.